2019
DOI: 10.1093/ct/qtz018
|View full text |Cite
|
Sign up to set email alerts
|

The Constitution of Organization as Informational Individuation

Abstract: Communication scholars, especially in organizational communication, call for a constitutive approach to communication that considers communicating and organizing as a single process. Yet, current theorizing seems unable to embrace that equivalence. As an alternative, we present an informationally grounded view of communication, drawing from French philosopher Gilbert Simondon. Doing so, we extend scholarship on the communicative constitution of organization by highlighting the importance of framing communicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 58 publications
(52 reference statements)
0
5
0
Order By: Relevance
“…And each of these actions entails a judgment, which is at once the cause, the reason, and the experience of this anaphor, of each moment in the progressive coming together of two modes of existence" (Souriau [1943] 2015, 219). These judgments and the differentiation they operate are crucial, first, because they are the conditions of creativity and, second, because they give meaning to action: what an action means is the difference it operates in its uptake (Bencherki and Iliadis 2021).…”
Section: éTienne Souriau and The Different Modes Of Existencementioning
confidence: 99%
See 1 more Smart Citation
“…And each of these actions entails a judgment, which is at once the cause, the reason, and the experience of this anaphor, of each moment in the progressive coming together of two modes of existence" (Souriau [1943] 2015, 219). These judgments and the differentiation they operate are crucial, first, because they are the conditions of creativity and, second, because they give meaning to action: what an action means is the difference it operates in its uptake (Bencherki and Iliadis 2021).…”
Section: éTienne Souriau and The Different Modes Of Existencementioning
confidence: 99%
“…The realization entails that dialogue is also a space where people express their solicitude for each other and support each other's pursuit of individuation (Arnett 2001; see also Bencherki and Iliadis 2021). In other words, dialogue is not only about reciprocity between already-constituted individuals (Weigand 2010) but also about the very ability of those individuals to exist as such.…”
Section: Introductionmentioning
confidence: 99%
“…Any effort to order and organize things, whether in everyday conversations or over longer timespans, thus inevitably also creates disorder and disorganization. However, rather than regret this fact, it should be recognized that it is crucial for organizations to be living, adaptive creatures (Bencherki & Iliadis, 2021;Vásquez et al, 2022).…”
Section: Continuity and Change In Text / Conversation Dynamicsmentioning
confidence: 99%
“…Insisting on the way communication performs an assemblage or arrangement of beings and articulates action among them shows that the synaptic mode of existence is at least as common and as constitutive of organizational reality as communication is. It also gives a hint as to the sort of empirical phenomena we may be interested in observing to look for modes of existence and their articulation: we must look for how modes of existence can 'speak' to each other to convey action (Bencherki, 2017;Bencherki & Iliadis, 2019).…”
Section: Finding 'Passages' Between Modes Of Existencementioning
confidence: 99%
“…By attempting to also capture how communication may happen within and through technology, bodies and other beings such a theory views communicating and organizing on the same terms. To this day, organizational communication research has mostly shown how communication in the conventional sense of 'what people say, write, or do' (Schoeneborn, Blaschke, Cooren, et al, 2014: 290) contributes to organizing processes, rather than understand communicating itself as coextensive with organizing (Bencherki & Iliadis, 2019). While the outline of such a perspective, remains to be sketched up, focusing on the organizations synaptic mode of existence may offer a way to pursue that agenda.…”
Section: What Organizing Meansmentioning
confidence: 99%